ANALISIS LAYANAN PERBANKAN BERBASIS BANKING NETWORK PADA PT. BANK RIAU KEPRI PEKANBARU - R. DINI ORBITHA; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The launch mobile Banking service Bank Riau Kepri Pekanbaru makescustomers PT Riau Kepri Pekanbaru, using the service felt a ATM Bank RiauKepri Pekanbaru hand where various banking transaction can be done throughmobile phones. Related to financial risk, customers will not be easily just like thatin determining banking services that will be used. The aim of this research is toknow and analyze banking services based- banking network In PT Bank RiauKepri Pekanbaru. Research method uses qualitative research method of research.This research will be done in Bank Riau Kepri Pekanbaru. While in the collectiondata that is by using interview technique to informers competent in directobservation and field. This research concluded Service Banking Network InBank Riau Kepri Pekanbaru can only be done by using HP (Hand Phone) have asystem and the smoothness service depends on signal and pulse that owned byusers mobile phones. Put PT Bank Riau Kepri Pekanbaru which continue toimprove service system especially about m-banking so that customers feelsatisfied, so that all its clients using m-banking more.Keywords : Analisis, Services, Banking Network, Riau, Pekanbaru